2013
DOI: 10.1103/physrevlett.110.160402
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence of a Single-Ion Qubit Immersed in a Spin-Polarized Atomic Bath

Abstract: We report on the immersion of a spin-qubit encoded in a single trapped ion into a spin-polarized neutral atom environment, which possesses both continuous (motional) and discrete (spin) degrees of freedom. The environment offers the possibility of a precise microscopic description, which allows us to understand dynamics and decoherence from first principles. We observe the spin dynamics of the qubit and measure the decoherence times (T1 and T2), which are determined by the spin-exchange interaction as well as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 32 publications
4
132
0
Order By: Relevance
“…Even the inclusion of spin degrees of freedom is possible in our method allowing for the study of a single-ion qubit in an atomic bath as recently reported in Ref. [20]. Finally, one could extend the setup to multiple ions making it possible, for instance, to investigate the polaron physics emerging in such hybrid systems.…”
Section: Conclusion and Outlooksmentioning
confidence: 94%
See 1 more Smart Citation
“…Even the inclusion of spin degrees of freedom is possible in our method allowing for the study of a single-ion qubit in an atomic bath as recently reported in Ref. [20]. Finally, one could extend the setup to multiple ions making it possible, for instance, to investigate the polaron physics emerging in such hybrid systems.…”
Section: Conclusion and Outlooksmentioning
confidence: 94%
“…Exploiting the state-dependent atom-ion interaction allows for the realization of quantum gates such * jschurer@physnet.uni-hamburg.de that the advantages of charged and neutral particles are combined [17] or makes it possible to control the tunneling in a bosonic Josephson junction such that the generation of entanglement between the atomic system and a single ion can be engineered [18,19]. Moreover, such systems offer possibilities to investigate and understand spin-decoherence processes and spin-exchange interactions at the fundamental level [20], aiming at negligible spin relaxation and efficient spin-exchange as desirable features for quantum information science. Besides, atom-ion systems are an excellent platform to simulate condensed-matter systems and Fröhlich polaron Hamiltonians more closely [21].…”
Section: Introductionmentioning
confidence: 99%
“…We derived formulas for the atom-ion CIR position (8) and (10) for a fixed atomic wave-number k = m A E / and numerically investigated their applicability in the region 0 ≤ E ≤ 2 ω ⊥ , namely up to the threshold for transverse atomic excitation. We note that these formulae are also applicable for atom-atom CIRs, where the inter-particle interaction is even more short-range.…”
Section: Atom-ion Confinement-induced Resonancesmentioning
confidence: 99%
“…The interest in combining in the laboratory ultracold atoms and ions is increased considerably in the last few years [1][2][3][4][5][6][7][8][9][10][11][12]. Their combination defines indeed a new quantum system characterised by an interaction with different energy and length scales with respect to ultracold atoms, which allows to study the formation of molecular ions [13,14], polarons [15], density bubbles [16], mesoscopic entanglement [17,18], novel ground state properties [19] and collective excitations [20], and quantum information processing [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The quantum dynamics of a single qubit or central spin coupled to a spin environment [1] has been widely studied theoretically in several different areas, including quantum information sciences [2][3][4][5][6][7][8][9], quantum decoherence [10][11][12][13][14][15][16][17][18][19], and excitation energy transfer [20][21][22]. One of the most promising candidates for quantum computation, solidstate spin systems, are inevitably coupled to their surrounding environment, usually through interactions with neighboring nuclear spins [6,23,24].…”
Section: Introductionmentioning
confidence: 99%